Florida 4-H Shooting Sports Instructor Training & Certification - Volunteer Leader Training Series - Julie Pigott Dillard; Heather C Kent; Julia S Kelly (EDIS)
A successful county Shooting Sports program is not possible without screened and trained volunteers to lead clubs. Before instructing youth in any Shooting Sports discipline and/or assisting on the range, a volunteer must meet the Florida 4-H youth protection screening requirements and complete the Florida 4-H Shooting Sports Level 1 Instructor Training. This 3-page fact sheet discusses volunteer recruitment, training, certification in other Shooting Sports disciplines, Level 2 certification, and job duties. Written by Julie P. Dillard, Heather C. Kent, and Julia S. Kelly, and published by the UF/IFAS 4-H Youth Development Department, January 2018. http://edis.ifas.ufl.edu/4h382